Strategi Pemasaran Media Sosial untuk Meningkatkan Brand Awareness pada Kanalima Coffee - Muhammad Daffa Syidad Wahyudi; Fahrul Ferdiansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Kanalima Coffee is a coffee shop located in Bandung, currently Kanalima Coffee is experiencing challenges and problems in improving brand image. This project runs as a response to the problems being faced by Kanalima Coffee with the objectives of (1) increasing brand awareness and engagement from the audience through content marketing and advertising campaigns, (2) increasing social media activities through planned and structured content creation according to the preferences, needs, and interests of the target audience, (3) implementing a rebranding project with the creation of a logo and tagline to increase competitiveness. The implementation succeeded in increasing the brand awareness of Kanalima Coffee through content marketing and advertising campaigns that had been carried out, and the results of this project showed an increase in Instagram engagement rate by 5.39% and TikTok by 35.73% from previously having no engagement rate data, as well as increased audience awareness of the Kanalima Coffee brand. Kanalima Coffee is known as a pioneer of practical, premium quality bottled coffee with a primary focus on customer satisfaction.